2008
DOI: 10.2337/db07-1287
|View full text |Cite
|
Sign up to set email alerts
|

Electronegative LDL Impairs Vascular Endothelial Cell Integrity in Diabetes by Disrupting Fibroblast Growth Factor 2 (FGF2) Autoregulation

Abstract: OBJECTIVE-L5, a circulating electronegative LDL identified in patients with hypercholesterolemia or type 2 diabetes, induces endothelial cell (EC) apoptosis by suppressing fibroblast growth factor (FGF)2 expression. FGF2 plays a pivotal role in endothelial regeneration and compensatory arteriogenesis. It is likely that vasculopathy and poor collateralization in diabetes is a result of FGF2 dysregulation.RESEARCH DESIGN AND METHODS-To investigate this mechanism, we isolated L5 from type 2 diabetic patients. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…In addition, L5 induced LOX‐1 expression in the thoracic aortic tissues of C57B6/J mice (Figure 1b; Supporting Information Figure S3D) but failed to induce endothelial senescence in LOX‐1 −/− mice. We previously showed that LOX‐1 serves as a receptor for L5 and mediates its entry into endothelial cells, subsequently inducing apoptosis (Li, Cao, Berndt, Funder, & Liu, 1999; Lu et al., 2008, 2009). Therefore, our results support that LOX‐1 mediates L5‐dependent endothelial senescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, L5 induced LOX‐1 expression in the thoracic aortic tissues of C57B6/J mice (Figure 1b; Supporting Information Figure S3D) but failed to induce endothelial senescence in LOX‐1 −/− mice. We previously showed that LOX‐1 serves as a receptor for L5 and mediates its entry into endothelial cells, subsequently inducing apoptosis (Li, Cao, Berndt, Funder, & Liu, 1999; Lu et al., 2008, 2009). Therefore, our results support that LOX‐1 mediates L5‐dependent endothelial senescence.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular senescence may contribute to adverse vascular remodeling before atherosclerosis development (Wang & Bennett, 2012). In the past, we showed that L5 can induce the apoptosis of endothelial cells and cardiomyocytes (Lee et al., 2012; Lu et al., 2008). In the present study, we treated HAECs with a lower concentration of L5 than was previously used, and cellular senescence but not apoptosis was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Our present findings have the important implication that regeneration of endothelial cells and upregulation of endothelial NO synthase expression via Akt signaling activated by vascular endothelial growth factor and other growth factors may not be suppressed by calcium antagonists. 24,25 The number of functional L-type calcium channels significantly decreased in dedifferentiated VSMCs and increased on differentiation. 26 This is consistent with our finding that nifedipine inhibits the dedifferentiation of differentiated VSMCs, thereby suppressing the development and progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This highly electronegative LDL has been called L5 because it is the fifth, most electronegative subfraction of LDL isolated by using anion-exchange chromatography (23 ). Plasma concentrations of L5 have been shown to be significantly increased in patients with cardiovascular risks, including smokers and patients with diabetes mellitus and hypercholesterolemia (23)(24)(25), and L5 concentrations are increased to an even greater extent in the plasma of patients with ST-elevation myocardial infarction (26 ).…”
Section: Biologic Interactions Of Crp Lox-1 and Atherogenic Ldlmentioning
confidence: 99%